Use of surface electromyography to estimate end-point force in redundant systems: comparison between linear approaches - Borzelli, Daniele; Gurgone, Sergio; De Pasquale, Paolo; Lotti, Nicola; d’Avella, Andrea; Gastaldi, Laura (Bioengineering, 2023)
Estimation of the force exerted by muscles from their electromyographic (EMG) activity may be useful to control robotic devices. Approximating end-point forces as a linear combination of the activities of multiple muscles acting on a limb may lead to an inaccurate estimation because of the dependency between the EMG signals, i.e., multi-collinearity. This study compared the EMG-to-force mapping estimation performed with standard multiple linear regression and with three other algorithms designed to reduce different sources of the detrimental effects of multi-collinearity ...
Gesehen am 05.12.2023